Standardised packaging, minimum excise tax, and RYO focussed tax rise implications for UK tobacco pricing. - Rosemary Hiscock; Nicole H Augustin; J Robert Branston; Anna B Gilmore (PLoS ONE)
Background Standardised packaging for factory made (FM) and roll your own (RYO) tobacco was fully implemented in the UK in May 2017. Around the same time, several changes to the tax system were applied (a Minimum Excise Tax (MET) for FM products and tax increases weighted towards RYO products). The tobacco industry claims that standardised packaging will lower prices (a disincentive for quitting) by commoditising the product, yet had itself taken advantage of the previous tax regime to achieve large profits from premium brands while also keeping some products' prices relatively low. Here we evaluate the impact of standardised packaging, the MET and the RYO focussed tax changes on price and industry profitability. Methods and findings Nielsen electronic point of sale (EPOS) data (May 2015 to April 2018) were used to calculate real (inflation adjusted) monthly price per stick overall, by cigarette type (FM and RYO) and by seven market segments. Trend estimation, using additive mixed models, assessed weighted average price (weighted by volume of sales) and tobacco industry net revenue changes. The beginning and end of the data series were compared in terms of: (a) average monthly price growth, (b) average monthly net revenue growth, and (c) undershifting and overshifting patterns after tax changes. FM and RYO real prices changed little over the 3-year period-overall prices rose by about 1p per stick. There was no evidence of commoditisation with prices of all FM segments (but not RYO) rising faster after the implementation of standardised packaging than immediately beforehand. The prices of the cheapest FM brands rose with the implementation of the MET. RYO price increases did not close the gap to FM pricing levels despite RYO focussed tax increases. Tax changes following the implementation of standardised packaging and the MET were more widely and quickly passed on to smokers in the form of higher prices than the tax change pre-implementation. The main limitations are first that because we do not know the exact mechanism by which Nielsen scales up sample data to provide UK estimates, we could only use data for a set three year period during which the same adjustments are made. Second, the tax and standardised packaging events were sometimes too close in time to separate their consequences statistically. Third, tobacco prices may also be affected by external factors such as changes in smokers' disposable income or availability of electronic nicotine delivery systems. Conclusions There was no long-term lowering of tobacco prices after the implementation of standardised packaging as predicted by the industry. The introduction of the MET was successful in increasing the price of the cheapest FM cigarettes and narrowing the price gap between FM brands. The RYO tax increases were, however, insufficient to narrow the price gap between RYO and FM. Overall, undershifting became less extensive indicating that tobacco industry manipulation of the tax system which had previously kept cheap products available had declined. This suggests that standardised packaging and a MET will likely contribute to further declines in UK tobacco use.